Screening to Identify Commonly Used Chinese Herbs That Affect ERBB2 and ESR1 Gene Expression Using the Human Breast Cancer MCF-7 Cell Line. (27th May 2014) - Chiu, Jen-Hwey; Chang, Chun-Ju; Wu, Jing-Chong; Liu, Hui-Ju; Wen, Che-Sheng; Hsu, Chung-Hua; Chen, Jiun-Liang; Tseng, Ling-Ming; Chen, Wei-Shone; Shyr, Yi-Ming
Abstract : Aim . Our aim the was to screen the commonly used Chinese herbs in order to detect changes in ERBB2 and ESR1 gene expression using MCF-7 cells. Methods . Using the MCF-7 human breast cancer cell line, cell cytotoxicity and proliferation were evaluated by MTT and trypan blue exclusion assays, respectively. A luciferase reporter assay was established by transient transfecting MCF-7 cells with plasmids containing either the ERBB2 or the ESR1 promoter region linked to the luciferase gene. Chinese herbal extracts were used to treat the cells at 24 h after transfection, followed by measurement of their luciferase activity. The screening results were verified by Western blotting to measure HER2 and ER α protein expression. Results . At concentrations that induced little cytotoxicity, thirteen single herbal extracts and five compound recipes were found to increase either ERBB2 or ESR1 luciferase activity. By Western blotting, Si-Wu-Tang, Kuan-Shin-Yin, and Suan-Tsao-Ren-Tang were found to increase either HER2 or ER α protein expression. In addition, Ligusticum chuanxiong was shown to have a great effect on ERBB2 gene expression and synergistically with estrogen to stimulate MCF-7 cell growth. Conclusion . Our results provide important information that should affect clinical treatment strategies among breast cancer patients who are receiving hormonal or targeted therapies.